Annual course of matric potential in differently used savanna oxisols in Brazil - Lilienfein, J; Wilcke, W.; Ayarza, Miguel Angel; Lima, SC; Vilela, Lourival; Zech, W. (Wiley, 1999)
Sustainable land use in periodically dry Brazilian savannas requires a water-saving management. We hypothesized that the annual course of matric potentials (?M) in very-fine, isohyperthermic Anionic Acrustoxes of Pinus plantations (PI), degraded (DP) and productive pastures (PP), no-till (NT) and conventional tillage (CT) cropping, and natural savanna (Cerrado, CE) differed significantly. On three plots in each of these land-use systems water input and ?M at the 0.15-, 0.30-, 0.80-, 1.2-, and 2.0-m depths was measured with tensiometers weekly between 27 Mar. 1997 and 28 Apr. 1998. Precipitation between 29 Apr. 1997 and 28 Apr. 1998 was 1562 mm, with only 210 mm in May to September, when ?M at the 0.15- and 0.30-m depths decreased to less than ?80 kPa in all systems; the lowest ?M at 2-m depth was ?57 kPa. During the monitored period, the PI soils had lower average ?M at the 0.8- to 2-m depths (?60 kPa) than those in CE (?46), indicating higher rainfall interception losses and higher transpiration. In CT, average ?M values at the 0.8- to 2-m depths (?29) were higher than in NT (?51) because of different crops and different soil management. Between June and November, ?M at the 2-m depth in CE decreased to a lower value (?42) than in vegetation-free CT (?22) and NT (?27). In DP and PP soils, ?Ms were similar to those in CE soils at all depths. The estimated average water storage in the upper 2 m during the monitored period was: 565 mm (CT) > 553 (PP) > 541 (DP) > 537 (CE) > 526 (NT) > 479 (PI). Our results show that mainly the vegetation type and tillage practices control the annual course of matric potential in differently used savanna Oxisols.